Assessment of reproductive outcomes and quality of life in patients after radical trachelectomy - A. L. Chernyshova; L. A. Kolomiets; Yu. M. Trushchuk; O. S. Dil; V. I. Chernov; E. S. Marchenko; T. L. Chekalkin; V. A. Antipov; S. E. Krasilnikov (ABV-press, 2022)
Cervical cancer occupies a leading position in the structure of oncogynecological pathology. Radical trachelectomy (RT) has entered the standards of treatment of invasive cervical cancer in patients of reproductive age. RT can be performed by transabdominal and laparoscopic approaches. The purpose of our study was a comparative assessment of the effectiveness and study of the quality of life in patients after RT. In total, 99 surgical interventions were performed using technologies developed at Oncology Research Institute, Tomsk National Research Medical Center of Russian Academy of Sciences. The features and results of treatment are described, including oncological efficacy, reproductive results (reproductive potential, peculiarities of the course of pregnancies and childbirth). The analysis of the study of the quality of life of patients after RT according to the criteria of modern questionnaires EORTC QlQC30 and QLQ-CX24.